Duality and Temporality: Evoking the Sublime through Pictures - Grave, Johannes (Aesthetica Preprint, 2024)
Pictures pose a particular problem for the question of the representability of the sublime (in Kant’s sense). Their dependence on a limited and immobile picture carrier seems to prevent any depiction of the sublime from the outset. The present contribution first asks what preconditions must be met in order to be able to speak of a successful evocation of the sublime. On this basis, it is explained why the choice of pictorial motifs that can be experienced as sublime in nature is not an adequate solution to this problem. Instead, the paper proposes that the mobilization of specific properties of pictures, i.e., their duality and their temporality, could render the evocation of sublime sensations conceivable. This approach is finally illustrated by reference to the examples of Caspar David Friedrich and J. M. W. Turner.